Effects of AZD3480 on cognition in patients with mild-to-moderate Alzheimer's disease: a phase IIb dose-finding study - Frölich, Lutz; Ashwood, Tim; Nilsson, Jonas; Eckerwall, Göran (Journal of Alzheimer's disease, 2011)
AZD3480 is a selective agonist of the central α4β2 and α2β2 neuronal nicotinic cholinergic receptors (NNRs). Its effects on cognition were investigated in 567 patients with mild-to-moderate Alzheimer's disease (AD) (Mini Mental State Examination [MMSE] 12–26). Mean baseline MMSE was 21 (SD ± 3.7), with 61% of patients having mild disease (MMSE 21–26). Mean age was 74 (range 58–85) years. Patients were randomized to one of 5 treatment groups: AZD3480 5 mg, 20 mg or 35/100 mg, donepezil 10 mg (active comparator) or placebo, and treated once daily for 12 weeks. The primary outcome measure was change from baseline at Week 12 on the AD Assessment Scale-Cognitive Subscale (ADAS-Cog). Neither AZD3480 nor donepezil showed a statistically significant improvement versus placebo on ADAS-Cog. Improvements in a number of secondary outcome measures (MMSE, AD Cooperative Study-Clinical Global Impression of Change (ADCS-CGIC) and Disability Assessment for Dementia [DAD]) were observed for AZD3480 and for donepezil. A post-hoc analysis on ADAS-Cog, excluding patients with very mild AD (MMSE 25–26) indicated improvement versus placebo for AZD3480 20 mg (−1.4, 95% CI: −3.0; 0.2) and donepezil (−1.0, 95% CI: −2.3; 0.3). AZD3480 was well tolerated. The study did not meet proof of concept criteria: since neither AZD3480 nor donepezil were statistically significantly superior to placebo on ADAS-Cog and was considered to be inconclusive. Further studies are required to determine the therapeutic potential of stimulating α4β2 receptors with NNRs in AD patients.
Gesehen am 22.05.2023